Perovskite nanocrystal and preparation method and application thereof
Patent Information
- Application Number
- CN202611075849.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]本申请实施例提供一种钙钛矿纳米晶及其制备方法、应用,以解决或缓解上面提出的一项或更多项技术问题
[0005]本申请实施例提供一种钙钛矿纳米晶及其制备方法、应用,以解决或缓解上面提出的一项或更多项技术问题。
Smart Images

Figure CN122898273A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of nanocrystalline luminescent materials technology, and in particular to a perovskite nanocrystal, its preparation method, and its application. Background Technology
[0002] All-inorganic perovskite nanocrystals (CsPbX3, X = Cl, Br, I) and organic-inorganic hybrid perovskites (ABX3, A = MA) + FA + (X = Cl, Br, I) possesses excellent optical properties such as a large absorption cross section, high fluorescence quantum yield, and tunable fluorescence emission wavelength. Among them, the all-inorganic system exhibits outstanding thermal and chemical stability, while the hybrid system combines excellent solution processability with flexible bandgap tuning. Both have shown great application potential in optoelectronic devices such as solar cells, light-emitting diodes, and lasers.
[0003] Currently, the preparation of all-inorganic perovskite nanocrystals mainly involves high-temperature injection and room-temperature supersaturated recrystallization. For organic-inorganic hybrid perovskite nanocrystals, existing synthetic routes also use lead halides as the core lead source, mostly following the technical framework of high-temperature injection or room-temperature recrystallization. These methods suffer from problems such as complex processes, high raw material costs, large solvent consumption, and poor batch-to-batch product stability, making it difficult to achieve large-scale preparation.
[0004] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of protection of this application. Summary of the Invention
[0005] This application provides a perovskite nanocrystal, its preparation method, and its application to solve or alleviate one or more of the technical problems mentioned above.
[0006] A first aspect of this application provides a perovskite nanocrystal. The perovskite nanocrystal comprises ABX3 and lauric acid, wherein the carboxylate ion in the lauric acid coordinates with the lead ion in the ABX3, where A is selected from cesium ions, rubidium ions, formamidinium ions, or methylamine ions, and X is selected from halogens; wherein the perovskite nanocrystal is formed by using lead laurate as a template and subjecting lead laurate to an in-situ conversion with a halide salt, and the lead laurate is obtained by a first reaction involving a lead source, lauric acid, and a solvent; the fluorescence quantum yield of the perovskite nanocrystal is at least 90%; and the emission wavelength of the perovskite nanocrystal is in the range of 400 nm to 700 nm.
[0007] The perovskite nanocrystals of this application exhibit high fluorescence quantum yield and can be directly used for subsequent device fabrication. This is because the perovskite nanocrystals of this application are formed by using lead laurate (Pb@LA) as a template and introducing halide salts (containing cesium ions, organic ammonium cations or formamidinium cations and halide anions). This allows the layered framework of Pb@LA to undergo in-situ transformation, guiding the reactant molecules to nucleate and grow along specific crystal planes. This method is simple, requires no large amount of solvent in the preparation process, and the product has good stability, thereby improving the luminescence of the perovskite nanocrystals.
[0008] A second aspect of this application provides a method for preparing perovskite nanocrystals. The method includes the following steps: performing a first reaction on a lead source, lauric acid, and a solvent to obtain lead laurate; dispersing the lead laurate in an antisolvent to form a suspension; using the lead laurate as a template, performing a second reaction on the suspension, a halide salt, and methanol, and causing the lead laurate to undergo an in-situ transformation with the halide salt to obtain perovskite nanocrystals. The perovskite nanocrystals comprise ABX3 and lauric acid, wherein the carboxylate ion in lauric acid coordinates with the lead ion in ABX3, where A is selected from cesium ions, rubidium ions, formamidinium ions, or methylamine ions, and X is selected from halogens.
[0009] The method in this application uses a pre-synthesized Pb@LA complex instead of the traditional expensive PbX2 as the lead source. This Pb@LA complex has a regular two-dimensional layered structure, constructed by coordination bonds between lead ions and lauric acid ligands, with the layers stacked by van der Waals forces. This structural characteristic allows it to act as a molecular-scale "reaction template": when a halide salt (containing cesium ions, organic ammonium cations, or formamidinium cations, and halide anions) is introduced, the layered framework of Pb@LA can undergo in-situ transformation, guiding reactant molecules to nucleate and grow along specific crystal planes. This template-induced transformation mechanism avoids the process of breaking strong ionic bond barriers through high-temperature injection, as required by traditional methods, thus enabling rapid and controllable generation of perovskite nanocrystals at room temperature. Simultaneously, because the lead ions in Pb@LA are in a pre-coordinated state, they have a lower activation energy when transforming into a perovskite lattice, which is beneficial for forming nanocrystalline products with low defect density and high crystallinity.
[0010] According to an embodiment of this application, the first reaction is carried out at room temperature for 2-24 hours.
[0011] According to an embodiment of this application, after the first reaction and before obtaining lead laurate, the process further includes washing and drying, wherein the washing is performed by centrifugal filtration, the drying temperature is 30°C-80°C, and the drying time is 6h-24h.
[0012] According to an embodiment of this application, the lead source includes lead acetate trihydrate, and the molar ratio of lead acetate trihydrate to lauric acid is controlled to be 1:(2-3) during the first reaction process.
[0013] According to embodiments of this application, the average particle size of the lead laurate is 1 μm-10 μm.
[0014] According to an embodiment of this application, the mass ratio of lead laurate to halide in the suspension is 100:(0.5-60).
[0015] According to embodiments of this application, the solvent includes one or more of methanol, ethanol, ethylene glycol, n-propanol, isopropanol, diethyl ether, or dichloromethane.
[0016] According to embodiments of this application, the antisolvent includes one or more of toluene, xylene, chlorobenzene, ethyl acetate, diethyl ether, or dichloromethane.
[0017] According to embodiments of this application, the halide salt includes CsX or MAX, where X is a halogen.
[0018] According to an embodiment of this application, the time for the second reaction is 1s-10s.
[0019] According to an embodiment of this application, after the second reaction and before obtaining perovskite nanocrystals, the process further includes filtration and drying. The filtration is carried out by centrifugal dispersion at a speed of 6000 rpm to 10000 rpm for 1 min to 5 min. The drying temperature is 30°C to 80°C.
[0020] A third aspect of this application provides an application of the perovskite nanocrystals described in the first aspect or prepared by the method described in the second aspect in optoelectronic devices. These optoelectronic devices include solar cells, light-emitting diodes, or lasers. Attached Figure Description
[0021] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.
[0022] Figure 1 These are schematic diagrams illustrating the in-situ transformation of lead laurate and halide in some embodiments; Figure 2 These are SEM images of lead lauryl laurate from Example 1 and perovskite nanocrystals from Examples 6, 7, and 9; Figure 3This is the infrared spectrum of lead laurate in Example 1; Figure 4 These are the XRD patterns of perovskite nanocrystals from Examples 1-4 and lead laurate from Example 1; Figure 5 Elemental EDS analysis of the perovskite nanocrystals in Example 1; Figure 6 These are the PL spectra of perovskite nanocrystals from Examples 1, 5, 7, and 8; Figure 7 These are the PL spectra of perovskite nanocrystals from Examples 2 and 10-14; Figure 8 These are the PL spectra of perovskite nanocrystals from Examples 3 and 15-16; Figure 9 These are the PL spectra of the perovskite nanocrystals in Examples 4 and 17-18. Detailed Implementation
[0023] The embodiments of this application are described in detail below, examples of which are illustrated in the accompanying drawings. In the drawings, for clarity, the dimensions of layers, regions, and elements, as well as their relative dimensions, may be exaggerated. Throughout, the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application. It should be noted that, unless otherwise specified, the embodiments and features in the embodiments of this application can be combined with each other.
[0024] It should be noted that the terms “comprising” and “having”, and any variations thereof, are intended to cover non-exclusive inclusion, for example, a process, method, system, product, or device that includes a series of steps or units is not necessarily limited to those steps or units that are explicitly listed, but may include other steps or units that are not explicitly listed or that are inherent to such process, method, product, or device.
[0025] In this application, when numerical intervals (i.e., numerical ranges) are involved, unless otherwise specified, the distribution of selectable numerical values within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.
[0026] A first aspect of this application provides a perovskite nanocrystal. The perovskite nanocrystal comprises ABX3 and lauric acid, wherein the carboxylate ion in the lauric acid coordinates with the lead ion in the ABX3, where A is selected from cesium ions, rubidium ions, formamidinium ions, or methylamine ions, and X is selected from halogens; wherein the perovskite nanocrystal is formed by using lead laurate as a template and subjecting lead laurate to an in-situ conversion with a halide salt, wherein the lead laurate is obtained by a first reaction involving a lead source, lauric acid, and a solvent; the fluorescence quantum yield of the perovskite nanocrystal is at least 90%; and the emission wavelength of the perovskite nanocrystal is in the range of 400 nm to 700 nm.
[0027] The perovskite nanocrystals of this application exhibit high fluorescence quantum yield and can be directly used for subsequent device fabrication. This is because the perovskite nanocrystals of this application are formed in situ by introducing a halide salt (containing cesium ions, organic ammonium cations, or formamidinium cations and halide anions) using lead laurate as a template. This allows the layered framework of Pb@LA to undergo in-situ transformation, guiding the reactant molecules to nucleate and grow along specific crystal planes. This method is simple, requires no large amounts of solvent, and produces a stable product, thus enhancing the luminescence of the perovskite nanocrystals. In the perovskite nanocrystals, ABX3 and lauric acid, with the carboxyl group in lauric acid coordinating with the lead ion in ABX3, are based on Pb@LA as a sacrificial template, providing highly ordered Pb. 2+ The ion array serves as a nucleation site, guiding [PbX6]. 4- Octahedral crystals undergo directional self-assembly with halide salts; simultaneously, the released long alkyl chains spontaneously coat the crystal surface, effectively passivating surface defects and significantly improving the dispersibility and stability of the resulting microcrystals.
[0028] The perovskite nanocrystals of this application are generated by in-situ conversion of lead laurate as a template and reacting with halide salts. The perovskite nanocrystals exhibit good fluorescence luminescence, with a fluorescence quantum yield of at least 90%. Furthermore, the perovskite nanocrystals can achieve luminescence across the entire visible spectrum (400nm-700nm). This is achieved by controlling the types and molar ratios of chlorine, bromine, and iodine in the halide salts, thereby precisely altering the band gap and controlling the emission wavelength.
[0029] The lead laurate in this application is described in detail in the second aspect by a first reaction of a lead source, lauric acid, and a solvent.
[0030] A second aspect of this application provides a method for preparing perovskite nanocrystals. The preparation method includes the following steps: subjecting a lead source, lauric acid, and a solvent to a first reaction to obtain lead laurate; The lead laurate is dispersed in an antisolvent to form a suspension; Using lead laurate as a template, a second reaction is carried out on the suspension, halide, and methanol, and lead laurate and halide undergo in-situ transformation to obtain perovskite nanocrystals. The perovskite nanocrystals include ABX3 and lauric acid. The carboxylate ions in lauric acid coordinate with the lead ions in ABX3. A is selected from cesium ions, rubidium ions, formamidinium ions, or methylamine ions, and X is selected from halogens.
[0031] The method in this application uses a pre-synthesized Pb@LA complex instead of the traditional expensive PbX2 as the lead source. This Pb@LA complex has a regular two-dimensional layered structure, constructed by coordination bonds between lead ions and lauric acid ligands, with the layers stacked by van der Waals forces. This structural characteristic allows it to act as a molecular-scale "reaction template": when a halide salt (containing cesium ions, organic ammonium cations, or formamidinium cations, and halide anions) is introduced, the layered framework of Pb@LA can undergo in-situ transformation, guiding reactant molecules to nucleate and grow along specific crystal planes. This template-induced transformation mechanism avoids the process of breaking strong ionic bond barriers through high-temperature injection, as required by traditional methods, thus enabling rapid and controllable generation of perovskite nanocrystals at room temperature. Simultaneously, because the lead ions in Pb@LA are in a pre-coordinated state, they have a lower activation energy when transforming into a perovskite lattice, which is beneficial for forming nanocrystalline products with low defect density and high crystallinity.
[0032] The method described in this application uses lead laurate as a template and reacts it with a halide salt to precisely control the band gap width of perovskite nanocrystals, thereby achieving luminescence across the entire visible spectrum. Furthermore, the products obtained in each step of the above method exist in powder form, independent of colloidal dispersion systems, and exhibit excellent storage stability and ease of transportation. The perovskite nanocrystals of this application possess a high fluorescence quantum yield (PLQY) and can be directly used in subsequent optoelectronic device fabrication.
[0033] According to embodiments of this application, a lead source, lauric acid, and a solvent are subjected to a first reaction to obtain lead laurate. In this step, lead source first reacts with lauric acid to form lead laurate.
[0034] In some embodiments, the lead source includes lead acetate trihydrate.
[0035] In some embodiments, the first reaction is carried out at room temperature for 2-24 hours. Examples include 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, and 24 hours. This process allows lauric acid to fully react with the lead source to form lead laurate template agent.
[0036] In some embodiments, after the first reaction and before obtaining lead laurate, washing and drying are further included, wherein the washing is performed by centrifugal filtration at a speed of 6000-10000 rpm for a time of 1-5 minutes.
[0037] Furthermore, the number of washes can be 2 to 4.
[0038] Furthermore, the drying temperature is 30℃-80℃, for example 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, etc., and the drying time is 6h-24h, for example 6h, 9h, 13h, 16h, 17h, 18h, 20h, 24h.
[0039] In some embodiments, the molar ratio of lead acetate trihydrate to lauric acid is 1:(2-3). For example, 1:2, 1:3, etc. In this step, by controlling the ratio of lead acetate trihydrate to lauric acid, a more stable product, lead laurate, is obtained, reducing the difficulty of purifying lead laurate due to insufficient lead, or the impact of excessive lauric acid on the crystal growth of titanium dioxide nanocrystals, which affects the performance of lead laurate.
[0040] In some embodiments, the average particle size of lead laurate is 1 μm-10 μm, such as 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, etc. This provides more reaction sites, further promoting the size uniformity of the perovskite nanocrystals.
[0041] According to embodiments of this application, lead laurate is dispersed in an antisolvent to form a suspension. Pre-dispersing lead laurate into a suspension helps to improve the yield of perovskite nanocrystals.
[0042] In some embodiments, the antisolvent includes one or more of toluene, xylene, chlorobenzene, ethyl acetate, diethyl ether, or dichloromethane.
[0043] According to the embodiments of this application, refer to Figure 1 Using lead laurate as a template, a second reaction is carried out on the suspension, halide, and methanol, and lead laurate and halide undergo in-situ transformation to obtain perovskite nanocrystals. The perovskite nanocrystals include ABX3 and lauric acid. The carboxylate group in lauric acid coordinates with the lead ion in ABX3. A is selected from cesium ion, rubidium ion, formamidinium ion, or methylamine ion, and X is selected from halogens.
[0044] In some embodiments, the second reaction uses lead laurate as a template to introduce a halide salt, causing an in-situ transformation of the layered framework of lead laurate to form perovskite nanocrystals. During the second reaction, the mass ratio of lead laurate to halide salt in the suspension is 100:(0.5-60), for example, 100:0.5, 100:1, 100:2, 100:4.5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:40, 100:50, 100:60, etc. By controlling the precursor concentration, a controllable transformation of the crystal dimension from quasi-two-dimensional to three-dimensional can be achieved. Excessive lead laurate (with relatively less halide salt) is beneficial for the formation of quasi-two-dimensional perovskites; simultaneously, it effectively passivates surface defects, resulting in high-quality perovskite materials with strong luminescent properties. If there is too little lead laurate (relatively excessive halide salts), the layered framework will be completely etched, losing its two-dimensional growth confinement effect. The crystal will grow excessively in the three-dimensional direction, and the dissociated laurate ions will not be enough to fully cover the crystal surface. The defect passivation effect will be insufficient, and the luminescence performance and stability of the product will decrease.
[0045] Optionally, the halide can be dissolved first, i.e., the halide is dissolved in methanol to form a halide methanol solution, and then the halide methanol solution is reacted with the suspension under ultrasonic conditions for 1-10 seconds.
[0046] In some embodiments, the halide includes CsX or MAX, where X is a halogen. For example, halide includes CsBr, CsCl, CsI, MABr, etc.
[0047] In some embodiments, after the second reaction and before obtaining perovskite nanocrystals, the process further includes filtration and drying. The filtration is performed by centrifugal dispersion at a speed of 6000 rpm-10000 rpm for 1-5 minutes. Filtration and drying can further improve the purity of the perovskite nanocrystals. The centrifugal dispersion can be performed multiple times, for example, 2-4 times.
[0048] Furthermore, the drying temperature is 30℃-80℃, for example, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, etc.
[0049] A third aspect of this application provides an application of the perovskite nanocrystals described in the first aspect or prepared by the method described in the second aspect in optoelectronic devices. These optoelectronic devices include solar cells, light-emitting diodes, or lasers.
[0050] Exemplary embodiments according to this application will now be described in more detail with reference to the accompanying drawings. It should be understood that these exemplary embodiments may be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein.
[0051] Example 1 S1. Pretreatment of the vessel: A 50mL glass beaker was selected as the reaction vessel. Before use, the beaker was washed with ethanol and deionized water in sequence, and then dried in a 60℃ oven until there were no visible water marks on the inner wall. It was then cooled and ready for use.
[0052] S2. Raw material weighing and proportioning: Weigh 1g of lauric acid and 0.948g of lead acetate trihydrate into two beakers as described above, according to the molar ratio of lauric acid to lead acetate trihydrate of 2:1.
[0053] S3. Dissolving: Add 12 mL of methanol to each of the above beakers, cover with plastic wrap to reduce solvent evaporation and prevent dust from entering; sonicate in an ultrasonic cleaner for 10 min to fully disperse the solid and promote dissolution, and obtain a homogeneous precursor mixture.
[0054] S4. Reaction: The lead acetate trihydrate methanol solution was poured into the lauric acid methanol solution under stirring at a constant speed of 800 rpm for 6 hours to obtain a white precipitate.
[0055] S5. Powder washing and drying: Collect the powder using a centrifuge at 8000 rpm and wash it three times with anhydrous ethanol to remove residual organic precursors or unbound components from the powder surface; then cover the centrifuge tube containing the powder with plastic wrap, prick it with a needle, and dry it at 50°C for 6 hours to obtain Pb@LA (lead lauryl acetate) powder.
[0056] S6. Pretreatment of glassware: 10mL glass bottles were selected as reaction vessels. Before use, the glass bottles were washed with ethanol and deionized water in sequence, and then dried in a 60℃ oven until there were no visible water marks on the inner wall. After cooling, they were ready for use.
[0057] S7. Raw material weighing: Weigh 100mg Pb@LA and add it to a glass bottle.
[0058] S8. Dissolution: Add 5 mL of toluene to the glass bottle, seal it, and sonicate it in an ultrasonic cleaner for 10 min to fully disperse the solid and promote dissolution, thus obtaining a precursor suspension.
[0059] S9. Reaction: Add 400 μL of a 15 mg / mL CsBr methanol solution (6 mg of CsBr) to a glass bottle and continue sonication for 10 seconds.
[0060] S10. Powder washing and drying: The powder was collected by centrifuge at 8000 rpm and washed three times with anhydrous ethanol to remove residual organic precursors or unbound components on the powder surface. Then, the centrifuge tube containing the powder was covered with plastic wrap, punctured with a needle, and dried at 50°C for 6 hours. The resulting perovskite nanocrystals were denoted as CsPbBr3@LA.
[0061] Example 2 Perovskite nanocrystals were prepared according to Example 1, except that two solutions, CsBr and CsCl, were added dropwise during the reaction process, with a Br / Cl molar ratio of 1.5:1. The resulting perovskite nanocrystals were denoted as CsPb(BrCl)3@LA.
[0062] Example 3 Perovskite nanocrystals were prepared according to Example 1, except that ethyl acetate was used as the antisolvent. 750 μL of a CsI methanol solution with a concentration of 20 mg / mL (15 mg of CsI) was added dropwise. The resulting perovskite nanocrystals were denoted as CsPbI3@LA.
[0063] Example 4 Perovskite nanocrystals were prepared according to Example 1, except that 100 μL of a 20 mg / mL MABr methanol solution (2 mg of MABr) was added dropwise. The resulting perovskite nanocrystals were denoted as MAPbBr3@LA.
[0064] Examples 5-9 Perovskite nanocrystals were prepared in accordance with the method of Example 1, except that the amount of CsBr added was 1.5 mg, 4.5 mg, 30 mg, 60 mg, and 90 mg respectively.
[0065] Examples 10-14 Perovskite nanocrystals were prepared in accordance with the method of Example 2, except that the molar ratio of Br / Cl was 0.1∶1, 0.4∶1, 1∶1, 3∶1, and 7∶1.
[0066] Examples 15-16 Perovskite nanocrystals were prepared in accordance with the method of Example 3, except that the amount of CsBr added was 30 mg and 45 mg respectively.
[0067] Examples 17-18 Perovskite nanocrystals were prepared in accordance with the method of Example 4, except that the amount of MABr added was 0.5 mg and 20 mg respectively.
[0068] Comparative Example 1 S1. Pretreatment of glassware: 10 mL glass bottles were selected as reaction vessels. Before use, the glass bottles were washed with ethanol and deionized water in sequence, and then dried in a 60℃ oven until there were no visible water marks on the inner wall. After cooling, they were ready for use.
[0069] S2. Weighing raw materials: Weigh PbBr2 (0.367g) and CsBr (0.213g) in a molar ratio of 1:1 and add them to a glass bottle.
[0070] S3. Dissolving: Add 5 ml of a DMSO / DMF mixed solution with a volume ratio of 4:1 to the glass bottle.
[0071] S4. Reaction: After heating and stirring at 80°C for 4 hours, the mixture was cooled to room temperature and then injected into isopropanol to obtain the product.
[0072] S5. Powder washing and drying: The powder was collected by centrifugation at 8000 rpm, washed three times with anhydrous ethanol, and dried at 50°C to obtain CsPbBr3 powder.
[0073] Figure 2 The images show SEM images of lead laurate from Example 1 and perovskite nanocrystals obtained from Examples 6 (4.5 mg), 7 (30 mg), and 9 (90 mg). The images show that the Pb@LA powder has a regular overall morphology, relatively uniform size distribution, and a dense surface. Comparing perovskite nanocrystals with 4.5 mg, 30 mg, and 90 mg of cesium bromide, it can be seen that with increasing CsBr content, the number of perovskite nanocrystals increases, while the lamellar structures gradually decrease and become smaller. This change corresponds to the continuous consumption of the Pb@LA template until it is completely depleted.
[0074] Figure 3 This is the infrared spectrum of lead laurate from Example 1. As can be seen from the graph, LA and Pb... 2+Complete deprotonation occurs after coordination: 1698 cm⁻¹ -1 The carbonyl stretching vibration peak at 1512 cm⁻¹ disappears. -1 A carboxylate vibration peak appears at 2849 cm⁻¹. -1 -2956cm -1 The characteristic alkyl chain vibrations of the region are preserved.
[0075] Figure 4 The XRD patterns of the perovskite nanocrystals in Examples 1-4 and lead laurate in Example 1 show that the obtained samples all have good phase purity.
[0076] Figure 5 The elemental EDS analysis of the perovskite nanocrystals in Example 1 shows that the perovskite was successfully and uniformly grown on the Pb@LA template.
[0077] Figure 6 The figures show the luminescence spectra of perovskite nanocrystals from Examples 1, 5, 7, and 8. As can be seen from the figures, the luminescence intensity of the CsPbBr3@LA sample first increases and then decreases with increasing CsBr dosage, reaching its peak at 6 mg CsBr. Further increases in CsBr to 30 mg and 60 mg result in a sharp decrease in luminescence intensity. This reflects that an appropriate amount of CsBr can achieve efficient luminescence through the confinement and passivation effects of the lead laurate template, while excessive CsBr will damage the two-dimensional structure of the template, weaken the quantum confinement effect, and increase defects, leading to a significant decrease in luminescence performance.
[0078] Figure 7 The figures show the PL spectra of the perovskite nanocrystals in Examples 2 and 10-14. As can be seen from the figures, the emission wavelength of CsPb(BrCl)3@LA can be continuously adjusted by regulating the Br / Cl molar ratio. With increasing bromine content, the emission peak gradually redshifts from ~420 nm (blue-violet light) to ~510 nm (green light), achieving continuous tunability of emission in the blue-green band. The peaks are sharp and exhibit good color purity at all ratios, verifying that this template method can precisely control the perovskite bandgap through halogen composition modulation.
[0079] Figure 8 The figures show the PL spectra of perovskite nanocrystals from Examples 3, 15, and 16. As can be seen from the figures, the emission peak of the samples is located in the red light band of about 660 nm under different CsI feed amounts, proving that the template method can successfully prepare iodine-based red light perovskite.
[0080] Figure 9The figures show the PL spectra of perovskite nanocrystals from Examples 4, 17, and 18. As can be seen from the figures, the emission peak of the samples is located in the green light band of about 530 nm under different MABr feed amounts, which proves that the template method can be extended to organic-inorganic hybrid perovskite systems, demonstrating that the method has wide applicability.
[0081] These PL spectra all demonstrate that by adjusting the type, ratio, and amount of halogen in the halide salt, the lead laurate template method can achieve continuously tunable luminescence across the entire visible wavelength range of 400nm-700nm.
[0082] By comparing the preparation methods of perovskite nanocrystals in the Examples and Comparative Example 1, it can be seen that the perovskite nanocrystals in the Examples can be prepared at room temperature and in air. The reaction can be completed instantly by simply injecting a methanol solution of CsBr into a Pb@LA toluene dispersion, without heating. Furthermore, the perovskite nanocrystals exhibit more uniform morphology and size, better phase purity, and higher and more stable luminescence. The preparation method of CsPbBr3 in Comparative Example 1 is more cumbersome and complex, requiring a larger amount of solvent. In addition, the Examples can achieve controllable preparation of perovskite with full visible spectrum luminescence in the 400nm-700nm range by adjusting the type and ratio of halogens, while Comparative Example 1 often only synthesizes CsPbBr3, a type of perovskite, and achieves a narrower luminescence range.
[0083] It should also be noted that the terms "some embodiments," "other embodiments," and "embodiments" used in this application refer to specific features, structures, or characteristics described in connection with those embodiments, which are included in at least one embodiment described in the general description of this application. The appearance of the same expression in multiple places in the specification does not necessarily refer to the same embodiment. Furthermore, when a specific feature, structure, or characteristic is described in connection with any embodiment, the intention is to suggest that implementing such a feature, structure, or characteristic in conjunction with other embodiments also falls within the scope of this application.
[0084] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.
[0085] It should also be noted that the above are merely preferred embodiments of this application and do not limit the scope of protection of this application. Any equivalent structural or procedural transformations made using the content of this application specification, or direct or indirect applications in other related technical fields, are similarly included within the scope of protection of this application.
Claims
1. A perovskite nanocrystal, characterized in that, It includes ABX3 and lauric acid. The carboxylate group in lauric acid coordinates with the lead ion in ABX3. A is selected from cesium ion, rubidium ion, formamidinium ion or methylamine ion, and X is selected from halogen. The perovskite nanocrystals are formed by using lead laurate as a template and allowing lead laurate to undergo an in-situ transformation with a halide salt. The lead laurate is obtained by a first reaction of a lead source, lauric acid, and a solvent. The fluorescence quantum yield of the perovskite nanocrystals is at least 90%; The emission wavelength of the perovskite nanocrystals is between 400nm and 700nm.
2. A method for preparing perovskite nanocrystals, characterized in that, Includes the following steps: The lead source, lauric acid, and solvent are reacted in a first reaction to obtain lead laurate; The lead laurate is dispersed in an antisolvent to form a suspension; Using lead laurate as a template, a second reaction is carried out on the suspension, halide, and methanol, and lead laurate and halide undergo in-situ transformation to obtain perovskite nanocrystals. The perovskite nanocrystals include ABX3 and lauric acid. The carboxylate ions in lauric acid coordinate with the lead ions in ABX3. A is selected from cesium ions, rubidium ions, formamidinium ions, or methylamine ions, and X is selected from halogens.
3. The preparation method according to claim 2, characterized in that, The first reaction was carried out at room temperature for 2-24 hours; And / or, after the first reaction and before obtaining lead laurate, washing and drying are further included, wherein the washing is performed by centrifugal filtration, the drying temperature is 30°C-80°C, and the drying time is 6h-24h.
4. The preparation method according to claim 2, characterized in that, The lead source includes lead acetate trihydrate, and the molar ratio of lead acetate trihydrate to lauric acid is controlled to be 1:(2-3) during the first reaction.
5. The preparation method according to claim 2, characterized in that, The average particle size of the lead laurate is 1μm-10μm.
6. The preparation method according to claim 2, characterized in that, The mass ratio of lead laurate to halide in the suspension is 100:(0.5-60).
7. The preparation method according to claim 2, characterized in that, The solvent includes one or more of methanol, ethanol, ethylene glycol, n-propanol, isopropanol, diethyl ether, or dichloromethane; And / or, the antisolvent includes one or more of toluene, xylene, chlorobenzene, ethyl acetate, diethyl ether, or dichloromethane; And / or, the halide salt includes CsX or MAX, where X is a halogen.
8. The preparation method according to claim 2, characterized in that, The second reaction takes 1-10 seconds.
9. The preparation method according to claim 2, characterized in that, After the second reaction, and before obtaining perovskite nanocrystals, filtration and drying are also included. The filtration is carried out by centrifugal dispersion at a speed of 6000 rpm-10000 rpm for 1 min-5 min. The drying temperature is 30℃-80℃.
10. The application of the perovskite nanocrystals of claim 1 or the perovskite nanocrystals obtained by the preparation method of any one of claims 2-9 in optoelectronic devices, wherein the optoelectronic devices include solar cells, light-emitting diodes or lasers.